An assessment of the risk mitigating factors in Ghana's bank industry - Samuel Erasmus Alnaa; Juabin Matey (Financial Internet Quarterly, 2023)
To maintain financial stability, banks need to recognize, assess, and mitigate potential losses, thus making risk control critical for long-term profitability as well as avoiding unexpected losses. This research examines the risk mitigating factors and performance of Ghanaian domestic banks in terms of capital adequacy, bank size, bank efficiency, and profitability, along with their association with systemic risk in the bank sector, as measured by the Z-score: Insolvency Risk - (µROA) plus capital asset ratio (equity capital divided by sum of all assets further divided by the standard deviation-(ƠROA) with a higher score for banks as a measure of bank stability. The study further explores the relationship between this ratio and the explanatory variables for a sample of 11 banks operating in Ghana between 2010 and 2021. Analysis of the data using the fixed effects model shows that profitability and bank efficiency are significant and affect the stability of banks positively. Bank size, on the other hand, is significant but negatively affects the stability of banks. Bank profitability is critical to stabilizing and protecting the banking sector from external shocks; as a result, this study suggests that bank management apply prudent practices to profitability-driven indicators and that the banking sector regulations be congruent with macro-prudential policies.
Keywords: G1; G210; G280; 330; Risk Mitigation; Performance; Domestic Commercial Banks